Effectiveness of Freshwater Mussel (Pilsbryoconcha exilis) as a Biofilter Medium in Improving Water Quality - Nuraisyah, Nuraisyah; Riyanto, Riyanto (Aquatic Life Sciences, 2025)
This study aimed to evaluate the effectiveness of the freshwater mussel (Pilsbryoconcha exilis) as a natural biofilter in improving water quality in Dusun II, Bandar Klippa Village, Deli Serdang Regency. The research was conducted from August to October 2020 using a Completely Randomized Design (CRD) comprising four treatments based on biofiltration duration: 0 days (control), 5 days, 10 days, and 15 days, each with four replications. The observed parameters included physical characteristics (turbidity, odor, color, total dissolved solids/TDS) and chemical properties (pH, iron/Fe, manganese/Mn, nitrite/NO₂⁻, and nitrate/NO₃⁻). Statistical significance was tested using ANOVA followed by DMRT. The results indicated that P. exilis significantly reduced turbidity and eliminated odor within 5 days of treatment. The pH also significantly decreased, although it remained within the safe threshold for clean water. Conversely, Fe and Mn concentrations did not change significantly, while nitrite and nitrate levels increased, presumably due to enhanced nitrification during filtration. Overall, P. exilis demonstrated potential as an effective biofilter for improving water's physical and chemical quality, with a 5-day filtration period identified as the optimal duration.